THE DINA AS A COMMUNITY GOVERNANCE MECHANISM FOR STRENGTHENING EDUCATION IN ATSIMO ANDREFANA, MADAGASCAR - Sulla, Razafitahindraza Erica Feyzine; Ratna, Hangivola Emyblonde; Esmati, Shahabuddin (JURNAL STRATEGI PEMBELAJARAN, 2025)
This study aims to explore the role of Dina as a community governance mechanism in supporting educational development in the rural municipalities of Milenaka, Ankililoaka, and Ankilimaliniky, located in the Atsimo-Andrefana region of Madagascar. Dina, a set of customary rules rooted in ancestral Malagasy traditions, has traditionally focused on maintaining public order, regulating social behavior, and resolving community conflicts. This study uses a qualitative case study approach, collecting data through semi-structured interviews, group discussions, and document analysis of local Dina regulations. 18 key informants participated, including mayors or vice mayors, Dina executive committee members, and representatives of youth, women, and persons with disabilities, ensuring diverse perspectives on governance and education. Thematic analysis was applied to identify patterns related to governance practices, community-based learning, and the integration of educational objectives within customary structures. indings reveal that Dina remains primarily associated with social regulation, yet its participatory mechanisms enable the transmission of social norms, promotion of school attendance, and engagement of marginalized groups. Women, youth, and persons with disabilities play critical roles in enhancing the educational potential of Dina, while challenges such as harsh enforcement practices, limited coordination with formal educational policy, and inconsistencies with constitutional principles constrain its effectiveness. The study concludes that reforming Dina to incorporate education-focused norms, fostering inclusive representation, and linking customary governance with local educational institutions can transform Dina into a culturally grounded, community-driven mechanism that supports both social cohesion and sustainable learning outcomes in rural Madagascar.